ANALISIS TINGKAT KESELAMATAN LALU LINTAS PADA PERSIMPANGAN MENGGUNAKAN METODE TCT (TRAFFIC CONFLICT TECNIQUE) - Muhammad Rizqy Meirawannur; Robby Robby; Ina Elvina (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Accidents often occur due to several factors, including factors such as drivers who are not alert in dealing with obstacles while driving, road geometry factors that do not meet standards, and vehicle factors such as being unfit for use and lacking maintenance. Based on these factors, the problem formulation focuses on the level of traffic safety at the Jl. Bukit Indah - Jl. Garuda - Jl. Bukit Kaminting intersection and the speed that occurs during conflicts at that intersection. The Traffic Conflict Technique method is used to analyze the safety level, and observations reveal that the intersection lacks traffic lights or signals. This increases the risk of accidents and reduces the level of road user safety. Looking at the average Time-to-Avoid (TA) required by road users, it is only 0.5 - 1.0 seconds, with a 31% percentage for evasion or avoidance. This poses a threat to road user safety. The vehicle speed during conflicts at the Jl. Bukit Indah - Jl. Garuda - Jl. Bukit Kaminting intersection is between 40 km/h and 50 km/h, with a 29% percentage as the highest speed.